The Localization of the Mitochondrial Proteins MRP1, KREL2 and LSU1 of Trypanosoma brucei - Kaltenbrunner, Sabine (Jihočeská univerzita, 2014)
The aim of this thesis was to investigate the localization of the mitochondrial proteins MRP1, KREL2 and LSU1 of Trypanosoma brucei. Furthermore, the proper functioning of the eYFP-tagged protein MRP1 was investigated.
The Localization of the Mitochondrial Proteins MRP1, KREL2 and LSU1 of Trypanosoma brucei
Keywords: Trypanosoma brucei; mitochondria; MRP1; KREL2; LSU1; Trypanosoma brucei; mitochondria; MRP1; KREL2; LSU1